Diiodothyropropionic acid in the management of cardiovascular disease. Issue 2 (June 2015) - Arora, Shitij; Agrawal, Manasi; Iqbal, Jameel; Bhandari, Peter; Mechanick, Jeffrey I.
<x xml:space="preserve">Abstract</x> Objective Cardiovascular disease is the leading cause of morbidity and mortality in the USA. Thyroid analogs have emerged as a potential new therapeutic agent for cardiovascular disease. Thyroid hormones beneficially influence cardiac contractility and serum lipids but can also confer harmful effects on cardiac tissue and bone. To circumvent these harmful effects of thyroid hormones, several thyroid analogs have been studied since the 1960s. This review focuses on one such thyroid analog, diiodothyropropionic acid (DITPA), which has shown promise in the management of heart failure. Materials and methods We conducted a systematic review of the literature using evidence-based criteria. Results Strong laboratory data exist supporting the role of DITPA in heart failure by improving systolic and diastolic heart function. DITPA significantly alters the myosin heavy chain ratio in the heart muscle to improve ventricular contractility. There is increasing evidence in support of the improvement in lipid profile in patients on DITPA. No proarrhythmogenic adverse effects were noted with the use of DITPA. Conclusion DITPA appears to be promising in enhancing cardiac output and hemodynamic stability for heart failure patients, with possible synergistic implications when combined with other heart failure medications. However, extensive human trials are needed to establish its role in the management of heart failure and establish its safety profile.